2016
DOI: 10.1159/000442293
|View full text |Cite
|
Sign up to set email alerts
|

Suicides and Suicide Attempts during Long-Term Treatment with Antidepressants: A Meta-Analysis of 29 Placebo-Controlled Studies Including 6,934 Patients with Major Depressive Disorder

Abstract: Background: It is unclear whether antidepressants can prevent suicides or suicide attempts, particularly during long-term use. Methods: We carried out a comprehensive review of long-term studies of antidepressants (relapse prevention). Sources were obtained from 5 review articles and by searches of MEDLINE, PubMed Central and a hand search of bibliographies. We meta-analyzed placebo-controlled antidepressant RCTs of at least 3 months' duration and calculated suicide and suicide attempt incidence rates, inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 66 publications
2
55
0
3
Order By: Relevance
“…The long lag period renders the standard of care antidepressants ineffective for suicidal patients who can’t afford to wait 2–6 weeks. Aside from the lag in antidepressant effects, there is insufficient evidence that antidepressants prevent suicide during long-term treatment 7 , and in many cases the antidepressant increases the risk of suicidal thoughts and actions 8 . Efficacy is another issue affecting depression treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The long lag period renders the standard of care antidepressants ineffective for suicidal patients who can’t afford to wait 2–6 weeks. Aside from the lag in antidepressant effects, there is insufficient evidence that antidepressants prevent suicide during long-term treatment 7 , and in many cases the antidepressant increases the risk of suicidal thoughts and actions 8 . Efficacy is another issue affecting depression treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, the US Food and Drug Administration (FDA) issued a black box warning regarding the risk of suicidality related to the use of antidepressants in children and adolescents [179]. The incidence of suicide and attempted suicide has been a frequently underreported adverse outcome across antidepressant RCTs [180]. The first association between the use of SSRIs and suicidality was reported in 1990 [181].…”
Section: Suicidalitymentioning
confidence: 99%
“…Two recent meta-analyses have not identified a clear increased risk of treatment-emergent suicidality in adult individuals treated with antidepressants in RCTs [180,183]. Notwithstanding that the use of antidepressants is efficacious for the treatment of MDD in adults, there is no clear evidence for either specific protective effects or increased risk related to suicidality.…”
Section: Suicidalitymentioning
confidence: 99%
“…The most recent meta-analysis on long-term RCTs of ADs found an increased rate of suicide attempts during long-term treatment with ADs. Nevertheless, the authors concluded that it is still unclear whether ADs increase the risk of suicide attempts (Braun et al, 2016). …”
Section: Introductionmentioning
confidence: 99%